A feather for a fan [large type] : a Washington territory story - Stover, Karla Wakefield (Wheeler Publishing, 2015)
In the late 1870s, twelve-year-old Hildy Bacom and her family leave Pennsylvania and head West, to New Tacoma on Commencement Bay in Washington Territory, a community that is barely four years old and with a population of approximately one hundred and fifty. Compared to Pennsylvania, everything in New Tacoma is different. The streets are muddy, there are few buildings, and some people live in hollowed-out cedar tree trunks. There are two small business districts, one on a wharf along Commencement Bay and the other up a steep hill on a bluff. Gradually Hildy adjusts to her new life and makes friends with some unusual people: Mrs. Money, who runs her store with a parrot on her head; Miss Rose, a lady of questionable reputation; and especially another twelve-year-old, Nell Tanquist. With Nell or alone, Hildy has adventures--with a bear, a skunk, and a lost Chinese baby. Hildy also turns entrepreneur and starts a little business baking and selling bread to waterfront laborers. Her dream is to have her own bakery. Then her life is complicated by two unexpected events: Samuel, the boy she is beginning to have feelings for, goes away, and her cousin, Elsie, arrives unexpectedly with a problem no one will talk about. Hildy deals with Elsie's health crisis, Samuel's return, and a livery stable fire using inner resources she didn't know she had. After a year in New Tacoma, Pennsylvania seems pretty tame. To her surprise, Hildy realizes she likes her new life.